On the effects and implications of UK Border Agency involvement in higher education. Issue 3 (13th January 2014) - Jenkins, Matt
<x xml:space="preserve">Abstract</x> This Commentary outlines the requirements that the UK Border Agency (UKBA) makes of universities if they wish to be permitted to teach non‐EU students. It argues that these requirements amount to a devolution of responsibility for border control from the UKBA to the university. The classroom is made a border site, and the border‐crossing student is subjected to continual monitoring. This has far‐reaching consequences for the character, ethos and life of the institution. These consequences are considered in light of research around the everyday spaces of neoliberal border control. It is argued that changes in the university mirror those found outside it and that resistance to such changes at the level of our institutions connect with resistance to border policies more generally.